Technical Efficiency of Rice Production Using the Stochastic Frontier Analysis Approach: Case In East Java Province - Fadilla Citra Melati; Yossita Prisma Mayninda (Universitas Muhammadiyah Ponorogo, 2020)
The aim of this study is to evaluate the efficiency of East Java rice production in 2018. This study uses a model for measuring the efficiency of stochastic frontier analysis (SFA). Empirical results of these findings indicate that the efficiency of rice production in East Java in 2018 was said to be very efficient in several districts and towns affected by the variable dry milled grain / GKG and irrigation variables, although there are still some districts and towns that cannot be said to be productive. Additionally, the explanatory variable of population growth affects the technical inefficiency of East Java rice production in 2018. Based on the results of this study's review, the practical implications for the government must continue to work to increase the scale and impact of efficiency on rice production, particularly on adding irrigated land to rice commodities, so that rice production can increase to the maximum and domestic food needs can be satisfied. Since the population of Indonesia continues to rise significantly, and rice is in fact a staple food for the people of Indonesia, rice production needs to be increased to ensure national social security. For this reason, it is necessary for the government to pay more attention to policies regarding the use and addition of paddy fields in order to keep optimum domestic rice production.